Analisis Pengembangan Pariwisata Halal Perspektif Maqashid Syariah Di Wisata Edukasi Inspirasi Preneurship Al Mumtaz Gunungkidul - Ayu, Navirta; Nurhidayatullah; Yuliani; Gustatnto, Edo Segara; Maulida Kirom, Atsanie (Educatia : Jurnal Pendidikan dan Agama Islam, 2024)
WEIPA halal tourism was chosen because of the opportunity and value of traveling, which is usually only a means of recreation, which is tried to be packaged by collaborating inspirational education and preneurship with sharia values ​​in a series of tour packages so that WEIPA comes with different tourism product services.This research is included in qualitative research using a descriptive approach. The subjects of this research are WEIPA managers and tourists, while the object of study is the development of WEIPA Halal Tourism from a Maqashid Syariah perspective.The research results show that in practice WEIPA tourism development is different from conventional because the services and products offered such as Field Trip packages (Batik, Screen Printing, Fashion, Catering and Rabbit Tourism) as well as Halal Culinary Tours at Pasar Ahad Pahing have been carried out in accordance with Al -Quran and As-Sunnah by paying attention to sharia values. In its implementation practice, WEIPA has paid attention to hifdz ad-din, hifdz al-'aql, hifdz an-Nafs, hifdz al-nasb and hifdz al-maal. Apart from that, analysis of the application of maqashid sharia values ​​has a positive impact on halal tourism. Al Mumtaz Preneurship Inspirational Educational Tourism.